THE FOURTH INDUSTRIAL REVOLUTION: A CASE FOR EDUCATIONAL TRANSFORMATION (The Pretoria Student Law Review, 2021)
In this article, I use the aims and objects of education to argue that educational empowerment involves skills development for 4th IR. At the backdrop of the meaning of ‘basic education’, I argue that any lack of adequate educational preparation for the 4th IR is an infringement on children’s constitutional right to basic education. Considering the wealth of jurisprudence centring on the right to basic education, it is further demonstrated that courts might be reluctant to grant remedies for the immediate realisation of curriculum change and other like-measures relevant for the 4th IR. This reluctancy is an aftermath of policy considerations to keep powers of the different arms of government purely separate. The conclusion reached is that: If the current judicial interpretive inflexibility and narrowness in approach to the right to basic education is maintained, and if this right is not fully fleshed out by the time the 4th IR is in full swing, the judiciary will not have an adequate, receptive and accommodating body of jurisprudence to refer to and rely on when adjudicating for educational changes required by the 4th IR. Courts will thus not be willing or positioned to find violations of the right as per the new de facto standards of the 4th IR. Consequences of this are: In the intermediate, the courts are unlikely or, on the jurisprudential approach, even unable, to find violations of the right to education where the Department of Education fails to take the necessary steps to give effect to the right; and that, given this judicial reticence and fettering, the jurisprudential position may continue to lag behind the dynamic lead of (global?) educational development in the wake of the 4th IR, meaning that the Department will likely not be compelled to catch-up to 4th IR progress if or when it, too, lags. And, assuming that landmark cases shift the jurisprudence on the right to education so as to catch-up to the 4th IR, outpacing a Department of Education which has been compliant with then previous jurisprudential standards, given the current and intermediate judicial reticence and fettering, the courts could plausibly then be left in a position of potentially ordering the executive to do the impossible and make-up the difference between a lagging education system and the 4th IR revolutionary requirements.
Keywords: educational empowerment; fourth industrial revolution; right to basic education; courts